Nursing of a patient with septic shock (1例脓毒症休克患者的护理体会) - DONG Chao (董超); LI Jing (李静); LI Ning (李宁) (Association of Integrative Nursing, 2022)
Sepsis shock is a life-threatening disease to ICU patients, which is one of the important factors causing the death of ICU patients. This paper summarized the nursing measures for a patient with septic shock, including nursing personnel arrangement, illness condition observation, medication care, skin care, mechanical ventilation nursing, and nutrition support. In addition to giving patients scientific and effective treatment, it is of positive significance to carry out detailed and comprehensive nursing measures for patients with septic shock. (脓毒症休克是 ICU 患者可能发生的一种严重性疾病, 是致使患者出现死亡的重要因素之一。本文总结了1例脓毒症休克患者的护理经验, 包括护理人员配置、病情观察、用药护理、皮肤管理、机械通气护理、营养支持等措施。临床中针对脓毒症休克的干预, 除了要给予科学有效的治疗措施外, 为患者展开细致化、全面化的临床护理措施, 并根据患者具体情况落实有针对性的护理具有积极意义。)